2010
DOI: 10.1063/1.3524211
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-doped single-crystalline SiGe/Si thermistor with high temperature coefficient of resistance and low noise level

Abstract: SiGe (C)/Si(C) multiquantum wells have been studied as a thermistor material for future bolometers. A thermistor material for uncooled Si-based thermal detectors with thermal coefficient of resistance of 4.5%/K for 100×100 μm2 pixel sizes and low noise constant (K1/f) value of 4.4×10−15 is presented. The outstanding performance of the devices is due to Ni-silicide contacts, smooth interfaces, and high quality multiquantum wells containing high Ge content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Although similar SiGe growth recipe was used for Si 0.72 Ge 0.28 /Si and Si 0.72 Ge 0.28 /Si 0.99 C 0.01 , the device containing C in the barrier benefits from wells with slightly higher Ge content (>28%) due to lower Si diffusion into the SiGe wells. Thus, growing Ge-delta layers at low temperature embedded in Si 1−y C y will be an ideal solution to create MQWs with very high TCRs and SNRs [17]. SIMS results indicated that the carbon amount at the interfaces (Si 0.99 C 0.01 /SiGe) is higher (as high as 2%) than compared to the barrier layer (Si 0.99 C 0.01 ).…”
Section: Resultsmentioning
confidence: 97%
“…Although similar SiGe growth recipe was used for Si 0.72 Ge 0.28 /Si and Si 0.72 Ge 0.28 /Si 0.99 C 0.01 , the device containing C in the barrier benefits from wells with slightly higher Ge content (>28%) due to lower Si diffusion into the SiGe wells. Thus, growing Ge-delta layers at low temperature embedded in Si 1−y C y will be an ideal solution to create MQWs with very high TCRs and SNRs [17]. SIMS results indicated that the carbon amount at the interfaces (Si 0.99 C 0.01 /SiGe) is higher (as high as 2%) than compared to the barrier layer (Si 0.99 C 0.01 ).…”
Section: Resultsmentioning
confidence: 97%
“…Somewhat surprisingly it was realized that alternating layers of Si and SiGe layers showed a large TCR of about 3% and that the TCR value in fact was exponentially related to the band gap offset in this type of heterostructure. Empirical studies over a relatively wide range of Ge content x in the the Si 1-x Ge x alloy confirm this [24][25][26]. In analogy with so-called quantum-well infrared photodetectors, employing direct conversion of photon energy into free carriers, the term quantum well thermistors was used.…”
Section: Theory Of Uncooled Microbolometersmentioning
confidence: 99%
“…For normal CVD growth conditions the maximum Ge concentration has been limited to about 30%, except for a few cases where carbon has been added to stabilize the lattice [24]. Nevertheless, the TCR values for all these samples show a saturating trend, where it is difficult to reach a repeatable TCR in excess of 3%/K.…”
Section: Materials For High Tcrmentioning
confidence: 99%
“…A vital issue in many cases for bolometers containing SiGe/Si MQW system is the control of the residual strain in the suspended membrane. Radamson et al (H. H. Radamson, Kolahdouz, Shayestehaminzadeh, Afshar Farniya, & S. Wissmar, 2010) reports the integration of C in the Si/SiGe stack (SiGe(C) / Si(C) MQWs) to create alternating tensile/compressive strain systems. The SiGe(C) layers were created through the intermixing of Si into the embedded Ge thin layers (grown by introducing GeH 4 without SiH 4 ).…”
Section: Thermal Excitationmentioning
confidence: 99%